“A lyrical interlude”; The Politics and Poetics of Sexual Education in Dulce Dueño by Emilia Pardo Bazán - Charnon-Deustch, Lou (Arenal. Revista de historia de las mujeres, 2013)
Emilia Pardo Bazán’s last novel Dulce Dueño (1911) constitutes a troubled gender fable that highlights issues related to women’s bodies and sex education in the early twentieth century. The protagonist’s quest for love demands of her extreme physical and mental sacrifice that lead to a state described here as that of an hysteric. As an hysteric, the protagonist withdraws her body from the conventional circulation expected of women of her age to become the bride of Christ. This article focuses especially on questions of bodily knowledge and abjection, tracing the protagonist’s route to the erotic scenario of the novel’s ending that marks paradoxically both the psychic success of her quest and the psychic annihilation of her will.